Respiratory Oscillometry in Newborn Infants: Conventional and Intra-Breath Approaches - Radics, Bence L.; Gyurkovits, Zita; Makan, Gergely; Gingl, Zoltán; Czövek, Dorottya; Hantos, Zoltán (Frontiers in Pediatrics, 2022)
Background: Oscillometry has been employed widely as a non-invasive and standardised measurement of respiratory function in children and adults; however, limited information is available on infants. Aims: To establish the within-session variability of respiratory impedance (Zrs), to characterise the degree and profile of intra-breath changes in Zrs and to assess their impact on conventional oscillometry in newborns. Methods: 109 healthy newborns were enrolled in the study conducted in the first 5 postpartum days during natural sleep. A custom-made wave-tube oscillometry setup was used, with an 8-48 Hz pseudorandom and a 16 Hz sinusoidal signal used for spectral and intra-breath oscillometry, respectively. A resistance-compliance-inertance (R-C-L) model was fitted to average Zrs spectra obtained from successive 30-s recordings. Intra-breath measures, such as resistance (Rrs) and reactance (Xrs) at the end-expiratory, end-inspiratory and maximum-flow points were estimated from three 90-s recordings. All natural and artefact-free breaths were included in the analysis. Results: Within-session changes in the mean R, C and L values, respectively, were large (mean coefficients of variation: 10.3%, 20.3% and 26.6%); the fluctuations of the intra-breath measures were of similar degree (20-24%). Intra-breath analysis also revealed large swings in Rrs and Xrs within the breathing cycle: the peak-to-peak changes amounted to 93% (range: 32-218%) and 41% (9-212%), respectively, of the zero-flow Zrs magnitude. Discussion: Intra-breath tracking of Zrs provides new insight into the determinants of the dynamics of respiratory system, and highlights the biasing effects of mechanical nonlinearities on the average Zrs data obtained from the conventional spectral oscillometry.